As concepções urbanísticas que impulsionaram o desenvolvimento do capitalismo e a reprodução da força de trabalho em São Paulo: sanear e excluir - Toledo, Rodrigo Alberto [UNESP] (My University, 2013)
This article aims to rank the main concepts in vogue in the city of São Paulo who contributed to the formulation of a shared urban oriented capitalist development and reproduction of the workforce. This way, it will discuss the main issues raised in the period, which is between the first decades of the XX Century to the end of the 1950s, trying to foresee how they worked as engineers and architects to incorporate the urbanistic proposals from Europe and the United States. And then, we will present, on the first four sections of this article, points of view that effectively impacted the paulista urban thought of the first half of the XX century: Sanitarism, pendular conception between the Mesologic Theory and the Microbian Theory; the Historicist formulation of Camillo Sitte; Howard´s garden-town and The French Experience. Our analyses were formulated having as a reference the broad systematization of bibliography and documents performed at the Arquivo Histórico Municipal (Intermediário) de Araraquara (Historical Municipal Archive from Araraquara), consultations at the the books of the library of the biblioteca da Faculdade de Arquitetura e Urbanismo da USP (USP Architecture and Urbanism College) and at the Faculdade de Ciências e Letras da UNESP, Araraquara-SP( College of Sciences and Languages from UNESP, campus Araraquara). The analisys of the performed research show that one urbanistic torrent at São Paulo State with clear influences from the conceptions that led the urbanistic debates in the first half of the XX Century. Although these conceptions compose a painting of urban transformations at São Paulo city and noticeably in some inland cities, previously to the solidification of a whole proposition for the city that was later called of Directive Plan.

O presente artigo pretende elencar as principais concepções urbanísticas que contribuíram na formulação de um pensamento urbanístico voltado para o desenvolvimento capitalista e para a reprodução da força de trabalho. Dessa forma, discutiremos as principais questões levantadas no período, desde as primeiras décadas do século XX até o final da década de 1950. Destarte, apresentaremos, nas três primeiras seções deste artigo, as concepções que efetivamente impactaram o pensamento urbano paulista da primeira metade do século XX: Sanitarismo, concepção pendular: entre a Teoria Mesológica e a Teoria Microbiana; A formulação historicista de Camillo Sitte; A cidade-jardim de Howard e a experiência francesa. Nossas análises foram elaboradas a partir de ampla sistematização bibliográfica e documental realizada no Arquivo Histórico Municipal (Intermediário) de Araraquara, consultas ao acervo da biblioteca da Faculdade de Arquitetura e Urbanismo da USP e da Faculdade de Ciências e Letras da UNESP de Araraquara, estado de São Paulo. As análises dos levantamentos sistematizados apontam que se efetivou uma corrente urbanista no Estado de São Paulo com nítidas influências das concepções que conduziram os debates dos urbanistas na primeira metade do século XX. Entretanto essas concepções compõem um quadro de transformações urbanas na cidade de São Paulo e, visivelmente, em algumas cidades do interior paulista, anteriores à solidificação de uma proposta interventora totalizante de cidade, denominada, posteriormente, de Plano Diretor.
Keywords: Urban thought; Urban planning; Cidade-jardim; Camillo de Sitte; Sanitarism; Pensamento urbano; Planejamento urbano; Cidade-jardim; Camillo de Sitte; Sanitarismo